Third World voices for children - McDowell, Robert E. (Robert Eugene), 1928-2014.; Lavitt, Edward; Isaac, Barbara Kohn. (London : Allison & Busby, 1973)
An anthology of folk tales from a variety of African countries, the West Indies, the United States, and the Polynesian people of Papua-New Guinea.
NLJCols20082021
Keywords: Tales; African Americans -- Folklore; Folklore -- Polynesia; Folklore -- Africa; Folklore -- United States; Folklore -- Polynesia; African Americans; Folklore; Tales; Polynesia; Negro tales & legends Anthologies. Juvenile literature; Children's nonfiction; Folklore